Dietary Total Antioxidant Capacity and Late-Life Cognitive Impairment: The Singapore Chinese Health Study. Issue 3 (7th April 2021) - Sheng, Li-Ting; Jiang, Yi-Wen; Feng, Lei; Pan, An; Koh, Woon-Puay
Abstract: Background: With the dramatically rapid rate of aging worldwide, the maintenance of cognitive function in old age is a major public health priority. The association between total antioxidant capacity (TAC) of midlife diet and cognitive function in late life is still unclear. Method: The study included 16 703 participants from a prospective cohort study in Singapore. Dietary intakes and selected supplementary use were assessed with a validated 165-item food frequency questionnaire at baseline (1993–1998). Two dietary TACs were calculated from the intake of antioxidant nutrients: the Comprehensive Dietary Antioxidant Index (CDAI) and the Vitamin C Equivalent Antioxidant Capacity (VCEAC). Cognitive function was assessed 20.2 years later using a Singapore-modified version of the Mini-Mental State Examination when subjects were 61–96 years old. Cognitive impairment was defined using education-specific cutoffs. Multivariable logistic regression models were utilized to estimate the associations between dietary TACs, component nutrients, and cognitive impairment. Results: A total of 2 392 participants (14.3%) were defined to have cognitive impairment. Both CDAI and VCEAC scores were inversely associated with odds of cognitive impairment in a dose-dependent manner. The odds ratio (95% confidence interval; p -trend) comparing the highest with the lowest quartile was 0.84 (0.73, 0.96; p -trend = .003) for the CDAI and 0.75 (0.66, 0.86; p -trend < .001) for the VCEAC. Higher intakes of vitamin C, vitamin E, carotenoids, and flavonoids were all inversely associated with cognitive impairment. Conclusions: Higher dietary TAC was associated with lower odds of cognitive impairment in later life in a Chinese population in Singapore.